Lethal and sublethal effects of metal-polluted sediments on Chironomus sancticaroli Strixino and Strixino, 1981 - de Souza Beghelli, Frederico Guilherme [UNESP]; Lopez-Dovál, Julio César; Rosa, André Henrique [UNESP]; Pompêo, Marcelo [UNESP]; Carlos, Viviane Moschini [UNESP] (Springer Nature, 2018)
The Cantareira Complex is one of the most important water supplies of the metropolitan region of São Paulo, Brazil. Previously, it was demonstrated that the sediments in this complex were polluted with metals and that Paiva Castro Reservoir—the last reservoir in the sequence, which receives water from the five previous reservoirs—was the reservoir with the greatest concentration of pollutants. Based on field data, it was noticed that copper concentrations in sediments were related to morphological alterations in chironomids. The present study provides novel monitoring methods and results for the complex by isolating the environmental and biological sources of variation. An adaptation of the in situ assay proposed by Soares et al. (Arch Environ Contam Toxicol 49:163–172, 2005), which uses a native tropical Chironomus species and low-cost materials, is also provided. The aim of this study was to isolate the effects of sediments from Paiva Castro on controlled populations of C. sancticaroli larvae using an in situ assay. A seven-day experiment was performed in triplicate. Third instar larvae were inoculated in chambers containing sediments from two distinct regions of Paiva Castro reservoir and a control site with sand. Five biological responses were considered: mouthpart alterations, larval length, width of cephalic capsule, mortality and total damage. The results suggest the effects of sediment toxicity on larvae include a reduction in length and a higher occurrence of total damage.
Keywords: Bio-indicator; Chironomid; Ecotoxicology; Metal pollution